Comparative performance of a primary-reader and second-reader paradigm of computer-aided detection for CT colonography in a low-prevalence screening population. - Miyake, Mototaka; Iinuma, Gen; Taylor, Stuart A; Halligan, Steve; Morimoto, Tsuyoshi; Ichikawa, Tamaki; Tomimatsu, Hideto; Beddoe, Gareth; Sugimura, Kazuro; Arai, Yasuaki (Japanese Journal of Radiology, 2013)
Objective: To compare the efficacy of computer-aided detection (CAD) for computed tomographic colonography (CTC) when employed as either primary-reader or second-reader paradigms in a low-prevalence screening population.Methods: Ninety screening patients underwent same-day CTC and colonoscopy. Four readers prospectively interpreted all CTC data sets using a second-reader paradigm (unassisted interpretation followed immediately by CAD assistance). Three months later, randomized anonymous data sets were re-interpreted by all readers using a primary-reader paradigm (only CAD prompts evaluated).Results: Compared with the average per-patient sensitivity for unassisted interpretation (0.57), both CAD paradigms significantly increased sensitivity: 0.78 (p < 0.001) for the second-reader paradigm and 0.83 (p < 0.001) for the primary-reader paradigm. There was no significant difference between CAD paradigms (p = 0.25). The average per-patient specificity for polyps ≥6 mm was significantly higher using the primary-reader paradigm than the second-reader paradigm (0.90 vs. 0.83, respectively, p = 0.006), with ROC AUCs of 0.83 and 0.68, respectively. Reading time using CAD as a primary-reader paradigm (median 1.4 min) was significantly shorter than both unassisted (median 4.0 min, p < 0.001) and second-reader paradigms (median 5.5 min, p < 0.001).Conclusion: CAD improves radiologist sensitivity in screening patients when used as either a second- or primary-reader paradigm, although the latter may improve specificity and efficiency more.